Early warning systems : stumbling blocks post-pandemic - Harjani, Manoj (2020)
Countries will need to address challenges around risk perception gaps and warning fatigue in order to raise their early warning systems’ effectiveness. Doing so will help them avoid strategic surprise from a future pandemic.